Hormesis: Is it an important factor in herbicide use and allelopathy? - Duke, Stephen; Cedergreen, Nina; Belz, Regina; Velini, Edivaldo [UNESP] (My University, 2006)
Stephen O. Duke, Nina Cedergreen, Edivaldo D. Velini, and Regina G. Belz describe the stimulatory effects of low doses of herbicides that are inhibitory or severely phytotoxic at normal use rates and consider the potential of this phenomenon. © 2006. Research Information Ltd. All rights reserved.
Keywords: Allelopathy; Environmental toxicology; Glyphosate; Herbicide; Hormesis